Distribution of the Yellowstone Grizzly Bear (2000-2014) - Interagency Grizzly Bear Study Team (USGS Science Data Catalog, 2017)
The grizzly bear distribution boundary delineates the estimated geographic extent of occupied range of the Yellowstone grizzly bear population for the period 2000-2014. The distribution boundary was generated to provide reliable estimations of grizzly bear occupancy throughout time and for use as a monitoring tool in grizzly bear management and conservation. The boundary was delineated by the Interagency Grizzly Bear Study Team (IGBST) using an interpolation method based on grizzly bear telemetry and GPS locations as well as verified observations and signs of grizzly bears inside the Greater Yellowstone ecosystem during 2000 to 2014.